Distributed renewable energies for off-grid communities planning, technologies, and applications - El Bassam, Nasir (Elsevier, 2013)
Energy is directly related to the most critical economic and social issues which affect sustainable development such as mobility, food production, environmental quality, regional and global security issues. Two-thirds of the new demand will come from developing nations, with China accounting for 30%. Without adequate attention to the critical importance of energy to all these aspects, the global, social, economic and environmental goals of sustainability cannot be achieved. Indeed the magnitude of change needed is immense, fundamental and directly related to the energy produced and consumed nationally and internationally. Today, it is estimated that more than two billion people worldwide lack access to modern energy resources. Distributed Renewable Energies for Off-Grid Communities provides various options and case studies related to the potential of renewable energies along with their environmental, economic and social dimensions. Case studies provide you with solutions to for future decentralized energy supply. Expanded coverage over previous work in the field to include coverage of rural and urban communities Provides new solutions for future decentralized energy supply.
Keywords: Small power production facilities.; Distributed generation of electric power.; Renewable energy sources.; Electric power distribution.; Energy development.; elektronické knihy; electronic books